Modeling and Control of Single-Stage Quadratic-Boost Split Source Inverters - Sherif M. Dabour; Majed A. Alotaibi; Amr A. Abd-Elaziz; Mahmoud A. Alshahat; Mahmoud Abdallah; Ali M. Eltamaly; Ayman S. Abdel-Khalik; Ahmed M. Massoud; Shehab Ahmed (IEEE Access)
This paper aims to develop the recently introduced Spilt-Source Inverter (SSI) topology to improve its boosting characteristics. New SSI topologies with high voltage gain are introduced in this paper. The proposed converters square the basic SSI’s boosting factor by utilizing an additional inductor, capacitor, and two diodes. Thus, the proposed converters are called Quadratic-Boost (or Square-Boost) SSIs (QBIs or SBIs). Four different QBI topologies are presented. One with continuous input current (CC-QBI), and the other draws a discontinuous input current (DC-QBI) but with reduced capacitor voltage stresses. This paper also introduces the small-signal model of the CC-QBI using state variables perturbance. Based on this model, the closed-loop voltage and current control approach of the dc-boosting factor are designed. Moreover, a modified space vector modulation (MSVM) scheme is presented to reduce the input current ripples. To evaluate the performance of the proposed topologies, a comparative study between them and the other counterpart from different perspectives is introduced. It can be found that the CC-QBI topology has superior boosting characteristics when operating with low input voltage compared with their counterparts. It has a higher boosting capability, lower capacitor voltages, and semiconductor stresses, especially when high voltage gains are required. These merits make the proposed topologies convenient to the Photovoltaic and Fuel-Cell systems. Finally, the feasibility of the suggested topology and the introduced mathematical model is verified via simulation and experimental results, which show good accordance with the theoretical analysis.